Propriedades elásticas da dentina humana e de um compósito reforçado por fibras de vidro como análogo - Merlo, Érlon Grando (2020)
evaluate the elastic properties of young and old human dentin and mechanical properties of a glass fiber-reinforced composite (GFRC) manufactured with different compositions. Methods: Samples with 2-mm of thickness from extracted healthy teeth were obtained from young patients (18-30 years) and old patients (40-60 years) (n=2), and used to obtaining the elastic modulus values by nanoindentation. Four different regions were measured: occlusal (O), pulp occlusion (PO), cervical (C) and pulp cervical (PC). Data were statistically evaluated using Kruskal-Wallis and Dunn's (α=0.05) tests. A glass fiber-reinforced composite (GFRC), obtained by the pultrusion process, was manufactured in four different compositions according to the rate of glass fibers (25% or 40%) and with (WF) and without (OF) filler particles in the matrix, generating the experimental groups: GFRC-OF25, GFRC-OF40, GFRC-WF25, GFRC-WF40. Mechanical properties such as density (ρ) (n=5), elastic modulus (E) and Poisson's ratio (ν) (n=5), Knoop microhardness (HK) (n=5), 3-point flexural strength (σ) and flexural elastic modulus (Ef) (n=10), and biaxial strength (σf) (n=10) were evaluated. Data were compared using Two-way Anova and Tukey (α = 0.05). Results: The mean values of elastic modulus obtained for old dentin ranged from 14.9 GPa to 24.75 GPa, with no statistical difference between the regions evaluated. The results obtained for young dentin ranged from 3.61 GPa to 25.0 GPa, with the lowest value obtained for the cervical region, statistically different from the occlusal-pulpal region. There was a statistical difference for the mean of the ρ and E values of the GFRC `s, with the highest values obtained for the GFRC`s that have a higher percentage of glass fibers in the composition, regardless of the presence or absence of filler particles. CRFVs with 40% of glass fibers had higher HK and Ef than the CRFVs with 25%. CRFVs with 25% of glass fibers had higher biaxial strength than CRFVs with 40% of glass fibers. Conclusion: Young and old dentin have no difference in the elastic modulus. With the exception of the cervical region, there is no difference in the elastic modulus of the regions measured in this study. The modification of the composition alters the mechanical properties of GFRC `s, and GFRC-WF40 was the most suitable material to simulate dentin in laboratory tests.